PENDAMPINGAN LITERASI DAN NUMERASI PADA MASA PANDEMI COVID 19 DI KABUPATEN MADIUN - C. Novi Primiani; Sudarmiani; Sanusi; Darmadi; Pujiati; Siti Marhamatul (Bajang Institute, 2022)
During the covid 19 pandemic, PGRI Madiun University has carried out community service programs through assistance in handling Covid-19 and online and offline Literacy & Numeracy assistance in Jiwan and Pilangkenceng sub-districts, Madiun district. The service's flagship work programs are Reading Corner, Introduction to E-learning, Classroom learning assistance, Home visits, Making learning videos, Education on health protocols, Making hand sanitizers using local materials, and Making simple Faceshields. The results of the activities show the success of abdimas. The Home visit work program has been well received by the parents of the students. The home visit program is carried out to assist students and parents independently at home so that they can overcome the learning crisis of students. The reading corner fosters student interest in reading, namely: as a facilitator for reading, as the closest reading material, comfortable, and attracts attention. The introduction of e-learning (google meet, zoom meeting, making digital presences, making questions via google forms and so on) has not been fully accepted quickly by students and teachers because of device constraints that do not support, many senior teachers are lacking in technology adaptation. Assistance in this class is guided by the tutor teacher. The civil servant teacher provides positive inputs to students and is assisted in overcoming all conditions encountered in the field. Making Learning Videos makes it easier for teachers and providing a teaching database made by students with the guidance of the tutor teacher to be uploaded on YouTube so that it can be accessed easily by students. Education on the application of health protocols carried out by socializing and providing posters related to health protocols, hand washing procedures and so on has increased student and community awareness in taking care of themselves, their families and the environment during the pandemic. The manufacture of hand sanitizers from local materials focuses on education, socialization, and providing trainings to provide antiseptics independently by using the main ingredients that are around them and additional materials that are abundantly available. The manufacture of a simple faceshield is carried out for the provision or manufacture of a faceshield as a repair tool from used 1.5-2L drinking bottles which are clear in color so that it is easier and cheaper.